2011
DOI: 10.1002/we.491
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for wind speed at turbine locations in a wind farm

Abstract: In wind farms, individual turbines disturb the wind field by generating wakes that influence other turbines in the farm. From a control point of view, there is an interest in dynamic optimization of the balance between fatigue and production, and an understanding of the relationship between turbines manifested through the wind field is hence required. This paper develops models for this relationship. The result is based on two new contributions: the first is related to the estimation of effective wind speeds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 10 publications
1
102
0
Order By: Relevance
“…In this study, an extended Kalman filter (EKF) is used to estimate the wind speed, as suggested in [20].…”
Section: Wind Speed Estimatormentioning
confidence: 99%
“…In this study, an extended Kalman filter (EKF) is used to estimate the wind speed, as suggested in [20].…”
Section: Wind Speed Estimatormentioning
confidence: 99%
“…It is however well described in [3]. In brief, v t The DI inflow part (19e), (19j) and (19k) is new while the rest of the aerodynamics (19l)-(19n) is standard except that the fictive wind v f is used for rotor torque and thrust.…”
Section: Extended Kalman Filtermentioning
confidence: 99%
“…The prediction error assessment is made for both simple simulation model data and for full scale experimental data. Notice that the EKF has a significant value on its own as it also estimates the effective wind speed (EWS) which is used for single turbine control [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The wind speed is modeled as v = v m + v t where v t is the turbulent wind and v m is a slowly varying mean wind speed as described in [15]. These are modeled aṡ…”
Section: B Stochastic Wind and Wave Modelsmentioning
confidence: 99%
“…Based on the available measurements, an EKF is implemented to estimate the unmeasured states as described in [15]. The deterministic model in Eq.…”
Section: E State Estimationmentioning
confidence: 99%